2017
DOI: 10.1111/jdv.14630
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of treatment goal alignment between Japanese psoriasis patients and their paired treating physicians

Abstract: BackgroundAppropriate goal‐oriented treatment strategies are important for optimal treatment outcomes and may prevent under‐treatment. As treatment goals vary by patient, a study to examine treatment goals is more meaningful when patients and their physicians are paired. There has not been any study that examines alignment between paired psoriasis patients and physicians in real‐world clinical practice using skin clearance as a treatment goal indicator.ObjectivesTo evaluate treatment goal alignment between pso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 22 publications
3
26
1
Order By: Relevance
“…We identified 56 studies involving 1,484 patients with either psoriasis (n = 1,147, range 1-104) or PsA (n = 337, range 1-89) ( Table 1). Study characteristics are shown in Table 1 [9][10][11][12][13][14][15]. Twenty five studies (46%) reported theoretical saturation, 35 (65%) reported multiple researcher involvement in data collection and analysis, and 45 studies (83%) provided participant quotations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 56 studies involving 1,484 patients with either psoriasis (n = 1,147, range 1-104) or PsA (n = 337, range 1-89) ( Table 1). Study characteristics are shown in Table 1 [9][10][11][12][13][14][15]. Twenty five studies (46%) reported theoretical saturation, 35 (65%) reported multiple researcher involvement in data collection and analysis, and 45 studies (83%) provided participant quotations.…”
Section: Resultsmentioning
confidence: 99%
“…Underdiagnosis of PsA and the variability in how rheumatologists and dermatologists prescribe disease modifying treatments may lead to undertreatment of PsA (8). While tighter dis ease control has been shown to improve disease activity (9), there remains a mismatch between patient and physician perception of the severity of the condition, potentially leading to differences in the perception of need for treatment escalation (10,11). International guidelines (12,13) emphasize the need for a shared decision making approach between clinicians and patients, which requires an understanding of the goals and values of patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study adopted efficacy using PASI‐90, as it has been commonly used in contemporary clinical trials as a more stringent efficacy endpoint . This measurement is also considered “the new standard of care” in actual clinical practice for moderate to severe psoriasis treated with biologics in Japan. Moreover, the study showed that the participants always preferred a higher probability in any type of efficacy parameter, dosing convenience with fewer administration frequency, a lower probability of serious infection and lower co‐payment.…”
Section: Discussionmentioning
confidence: 99%